1997
DOI: 10.1192/bjp.171.5.444
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 5-HT2 receptor imaging in major depression: focal changes in orbito-insular cortex

Abstract: Pathophysiology of depression may involve changes in 5-HT2 receptor in brain regions selectively implicated in mood regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(80 citation statements)
references
References 27 publications
(4 reference statements)
2
72
0
3
Order By: Relevance
“…In line with this, an investigation with b-CIT single photon emission computed tomography reported evidence for a reduction in the activity of the transpoter in patients with depression compared with healthy controls (Malison et al, 1998). Moreover, an increase in the density of postsynaptic cortical 5-HT2 receptor-binding sites of depressed suicide victims and unmedicated depressed patients have been observed by post-mortem studies (Stanley and Mann, 1983;Yates et al, 1990) and PET investigations (Biver et al, 1997). It has been suggested that upregulation of cortical 5-HT2 receptors in depression is an adaptive response to reduced synaptic serotonin (Owens and Nemeroff, 1994).…”
Section: Introductionmentioning
confidence: 70%
“…In line with this, an investigation with b-CIT single photon emission computed tomography reported evidence for a reduction in the activity of the transpoter in patients with depression compared with healthy controls (Malison et al, 1998). Moreover, an increase in the density of postsynaptic cortical 5-HT2 receptor-binding sites of depressed suicide victims and unmedicated depressed patients have been observed by post-mortem studies (Stanley and Mann, 1983;Yates et al, 1990) and PET investigations (Biver et al, 1997). It has been suggested that upregulation of cortical 5-HT2 receptors in depression is an adaptive response to reduced synaptic serotonin (Owens and Nemeroff, 1994).…”
Section: Introductionmentioning
confidence: 70%
“…Some studies have found decreased 5-HT 2A receptor binding in depressed patients more diffusely (Larisch et al, 2001;Yatham et al, 2000;Moresco et al, 2000). Biver et al (1997b) found decreased 5-HT 2A receptor binding in a single region of the frontal cortex. Methods of analysis and selectivity of radiotracers used varied widely across these reports and may be a source of the variability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 F]altanserin has high affinity (K i ¼ 0.13 nM) and selectivity for imaging 5-HT 2A receptors (Lemaire et al, 1991), and has in vivo binding in rat brain comparable to in vitro mapping of 5-HT 2A receptors (Biver et al, 1997a). It also has good in vivo test-retest reliability in humans (Smith et al, 1998) with an established literature in human brain mapping using PET (Biver et al, 1997b;Smith et al, 1998;Meltzer et al, 1999;Larisch et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of 5-HT 2A receptor binding in major depression has been explored in several cross-sectional postmortem (Stockmeier, 2003) and imaging studies (Attar-Levy et al, 1999;Biver et al, 1997;Yatham et al, 2000;Messa et al, 2003) of which two studies took into account measures of negativistic thinking. A recent study by Bhagwagar et al (2006), in un-medicated, euthymic patients recovered from depression, support that a higher frontolimbic 5-HT 2A receptor level may be a trait factor of the susceptibility to develop depression and correlate positively with measures of negativistic thinking.…”
Section: Discussionmentioning
confidence: 99%